[Turin, capital of hydrogeology: the story of Flowpath 2025] - M. Lasagna; G. Taddia; D. Cocca; E. Egidio; D. A. De Luca; M. Gizzi; F. Vagnon; S. Rusi; S. Da Pelo (Acque Sotterranee, 2025)
[Article in Italian]